Details of the enclosure wall of the Bhandasar Temple Complex - Temples of India Project Team (Jio Institute, 2024)
Details of the enclosure wall of the Bhandasar Temple Complex. The floral pattern merlons are only found on the east-facing enclosure wall. These are painted red to resemble brickwork probably.